The corpus callosum in people with congenital adrenal hyperplasia (CAH) - Eileen Luders; Debra Spencer; Caitlin Dale; Ieuan A. Hughes; Ajay Thankamony; Umasuthan Srirangalingam; Helena Gleeson; Helen Simpson; Melissa Hines; Florian Kurth (Scientific Reports)
Abstract Congenital Adrenal Hyperplasia (CAH) is a group of genetic disorders that affect the adrenal glands. CAH manifests in abnormal levels of cortisol and androgens and is accompanied by white matter alterations. However, no CAH study has specifically targeted the corpus callosum, the brain’s largest white matter fiber tract. To bridge that gap in the literature, we investigated callosal morphology in 53 individuals with CAH and 53 matched controls (66 women, 40 men). In addition to calculating areas for seven callosal subsections, we estimated the callosal thickness at 100 equidistant points. All statistical analyses were conducted while co-varying for age and total brain volume and applying corrections for multiple comparisons. There were no significant effects of biological sex and no significant group-by-sex interactions. However, there was a significant effect of group, both for area measures and thickness estimates, indicating smaller dimensions within the callosal splenium and isthmus in people with CAH. Our findings corroborate previous studies highlighting white matter alterations in CAH and may suggest that callosal integrity is compromised due to potentially adverse effects of glucocorticoids, a standard treatment for both men and women with CAH.